Pharmacology and Pharmacy Research in India: A Scientometrics Study - Sab M, Chaman; Kumar P, Dharani; Biradar, B. S. (Journal of Pharmacy Practice and Community Medicine)
Analyses the Indian publications output in Pharmacology and Pharmacy during 2004-18 on several parameters including contribution and citation impact of most productive countries, India’s overall contribution, its growth pattern, citation impact, the share of international collaboration, identification of significant participating countries in India’s international collaboration, most productivity and impact of leading Indian institutions and authors. The Web of Science Citation Database has been used to retrieve the data for 15 years (2004-18) by searching the keywords “Pharmacology and Pharmacy” in combined Title, Abstract and Keywords field. The Indian publications output in Pharmacology and Pharmacy research consisted of 37,734 papers during 2004-18, which increased from 1045 papers in 2005 to 3,042 papers in 2014, which decreased from 2,898 during 2015 and 1,817 during to 2018. The share of Indian overall Pharmacology and Pharmacy research was 11.56% during 2003-12, which increased from 10.43% during 2003-07 to 12.18% during 2008-12. Indian research out put on Pharmacology and Pharmacy is quite low in the global context as reflected from its publication output per thousand publication (0.001) and its world publication share (3.28%) during 2004 – 2018. Also, the impact and quality of Indian research is low compared to select development and developing countries.
Keywords: Pharmacology; Pharmacy; India; Research output; Scientometric analysis